Chronic crude garlic-feeding modified adult male rat testicular markers: mechanisms of action - El May Michèle V; Benahmed Mohamed; Amara Souheila; Hammami Imen; Mauduit Claire (BMC, 2009)
Abstract Background Garlic or Allium sativum (As) shows therapeutic effects such as reduction of blood pressure or hypercholesterolemia but side-effects on reproductive functions remain poorly investigated. Because of garlic's chemical complexity, the processing methods and yield in preparations differ in efficacy and safety. In this context, we clarify the mechanisms of action of crushed crude garlic on testicular markers. Methods During one month of treatment, 24 male rats were fed 5%, 10% and 15% crude garlic. Results We showed that crude garlic-feeding induced apoptosis in testicular germ cells (spermatocytes and spermatids). This cell death process was characterized by increased levels of active CASP3 but not CASP6. Expression of the caspase inhibitors BIRC3 and BIRC2 was increased at all doses of As while expression of XIAP and BIRC5 was unchanged. Moreover, expression of the IAP inhibitor DIABLO was increased at doses 10% and 15% of As. The germ cell death process induced by As might be related to a decrease in testosterone production because of the reduced expression of steroidogenic enzymes (Star, Cyp11a, Hsd3b5 and Hsd17b). Evaluation of Sertoli markers showed that TUBB3 and GSTA2 expression was unchanged. In contrast, AMH, RHOX5 and CDKN1B expression was decreased while GATA4 expression was increased. Conclusion In summary, we showed that feeding with crude garlic inhibited Leydig steroidogenic enzyme expression and Sertoli cell markers. These alterations might induce apoptosis in testicular germ cells.